KANDUNGAN NUTRIEN FESES DAN KONSUMSI BAHAN ORGANIK RANSUM PADA KELINCI NEW ZEALAND WHITE AKIBAT PEMBERIAN PAKAN DENGAN SUMBER SERAT YANG BERBEDA - Sutaryo Sutaryo; Lintang Sulistyaning Utami; Agung Purnomoadi; Dewi Hastuti (MEDIAGRO, 2018)
The aim of this study was to evaluate feces quality and organic matter intake of New Zealand White (NZW) rabbit fed different fibre source in the ration. The treatments were T1: coffee peel as fibre source, T2: coffee and been peel (1:1) as fibre source (1:1) and T3: been peel as fibre source. Five teen NZW 50-60 days old with 1.2 kg initial body weigh were divided randomly in to three treatments. Result of this experiment were no significant effect (P>0.05) of treatment on crude protein, crude fibre of feces and organic matter intake but gave significant effect (P<0.05) on feces crude fat.It can be concluded that the feces quality of rabbit fed different fibre source in the ration was relatively same, therefore it doesn’t need pre-treatment when it will further processed.